Inhibition of AXUD1 attenuates compression-dependent apoptosis of cementoblasts - Korb, Katja; Katsikogianni, Eleni; Zingler, Sebastian; Daum, Edith; Lux, Christopher J.; Hohenstein, Axel; Erber, Ralf (Clinical oral investigations, 2016)
Root resorptions are common undesirable side effects of orthodontic treatment. In most patients, these defects are repaired by cementoblasts. However, in 1-5 % of patients, the repair fails. The repair mechanism is not well understood. Apoptosis of cementoblasts might contribute to an impaired repair of root resorptions induced by orthodontic forces.
Gesehen am 15.05.2020